2010
DOI: 10.1007/s11010-010-0562-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-C promotes the growth and invasion of gallbladder cancer via an autocrine mechanism

Abstract: Vascular endothelial growth factor-C (VEGF-C) has a well-defined action on neoplastic lymphangiogenesis and angiogenesis through VEGF receptor-3 (VEGFR-3) and VEGFR-2, respectively, which are generally expressed in endothelial cells. The function of the VEGF-C/receptors pathway in tumor cell types is largely unknown. In this study, we examined the expression and role of VEGF-C/receptors in gallbladder cancer (GBC) cells. We examined the expression of VEGF-C in 50 surgical specimens from gallbladder cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Several of these effects were described earlier and confirmed in our study. In fact, similar to other investigators (Su et al, 2006;Timoshenko et al, 2007;Kodama et al, 2008;Chen et al, 2010), we observed that in vitro cancer cells with downregulated VEGF-C show reduced proliferation and/or migration. Using in vivo analysis, which allows to reveal not only autocrine but also paracrine effects, we found that in addition to deceleration of tumor growth, VEGF-C downregulation caused inhibition of lymphangiogenesis in tumor and surrounding tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several of these effects were described earlier and confirmed in our study. In fact, similar to other investigators (Su et al, 2006;Timoshenko et al, 2007;Kodama et al, 2008;Chen et al, 2010), we observed that in vitro cancer cells with downregulated VEGF-C show reduced proliferation and/or migration. Using in vivo analysis, which allows to reveal not only autocrine but also paracrine effects, we found that in addition to deceleration of tumor growth, VEGF-C downregulation caused inhibition of lymphangiogenesis in tumor and surrounding tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Initially, it was thought that VEGF-C synthesized in cancer cells promotes metastasis mainly through induction of lymphangionenesis in tumor tissues and sentinel lymph nodes that facilitated the spread of cancer cells via the lymphatic vessels (Mandriota et al, 2001;He et al, 2002;Hoshida et al, 2006). However, several recent studies reported that autocrine regulation of cancer cells migration via VEGF-C/VEGFRs is an important inducer of tumor cell proliferation, invasion and metastasis (Timoshenko et al, 2007;Kodama et al, 2008;Su et al, 2006Su et al, , 2008Chen et al, 2010). This stimulation of cancer cell motility is partly mediated by activation of VEGFR3-Src-p38MAPK-C/EBP-contactin-1 pathway (Su et al, 2006); however, other possible mechanisms of induction of cell locomotion by VEGF-C remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the GBC-SD cell lines in China, the human primary GBC cell lines SGC-996, isolated from the primary mastoid adenocarcinoma of the gallbladder obtained from a 61-yearold female patient in Tongji Hospital, were successfully established by our groups in 2003. Furthermore, SGC-996 cells were in accordance with the general characteristic of the cell line in vivo and in vitro and applied in several laboratory investigations (29,30). Our groups have shown evidence of VM in three-dimensional matrix of highly aggressive GBC-SD or poorly aggressive SGC-996 cells preconditioned by highly aggressive GBC-SD cells in vitro and GBC-SD nude mouse xenografts in vivo (31).…”
Section: Introductionsupporting
confidence: 62%
“…Accumulating evidence has shown that upregulated VEGF-C, a lymphangiogenic growth factor, positively correlates with regional LN metastasis and poor survival in multiple human malignancies, including bladder cancer (9,(11)(12)(13)(14)(15). Several groups have reported that when VEGF-C signaling is blocked via either small interfering RNAs or a neutralizing antibody to VEGF-C or VEGF-R3, the lymphatic-based metastatic spread of human malignancies can be inhibited (9,(16)(17)(18). Importantly, the VEGF-C monoclonal antibody (VGX-100) has been tested in a phase I clinical trial for advanced or metastatic solid tumors that are refractory to standard treatments (ClinicalTrials.gov NCT01514123).…”
Section: Introductionmentioning
confidence: 99%